1980
DOI: 10.1007/bf02565519
|View full text |Cite
|
Sign up to set email alerts
|

Afferent and efferent nerve endings of the outer hair cells in the rahbit

Abstract: The afferent and efferent nerve endings of the outer hair cells of the rabbit were investigated electron-microscopically. The afferent nerve ending was 1.4 X 2.0 microns in size and contained small vesicles, spherical mitochondria, and occasionally multivesicular bodies. The partially thick and dense membranes on either side of the synaptic cleft were observed and this region of the synaptic cleft was high in electron density. This area was considered to be an active zone of the afferent nerve ending. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Additionally, it has been shown that myelinated axons are more vulnerable to hypoxic stress than unmyelinated axons (Waxman et al, 1991). Studies employing immersion fixation or delaying fixation of tissue until lengthy dissections are completed seem more likely to encounter MVBs in axons (Chu-Wang and Oppenheim, 1980; Omata and Schatzle, 1980; Schmied and Holtzman, 1987; Sandow et al, 2000). Additionally, many of the studies that report MVBs in myelinated axons introduced exogenous proteins, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that myelinated axons are more vulnerable to hypoxic stress than unmyelinated axons (Waxman et al, 1991). Studies employing immersion fixation or delaying fixation of tissue until lengthy dissections are completed seem more likely to encounter MVBs in axons (Chu-Wang and Oppenheim, 1980; Omata and Schatzle, 1980; Schmied and Holtzman, 1987; Sandow et al, 2000). Additionally, many of the studies that report MVBs in myelinated axons introduced exogenous proteins, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…MVBs have also been noted among the afferent and efferent innervation of outer hair cells within the mammalian inner ear (Omata and Schatzle, 1980) and in cardiac ganglion terminals (Pauziene and Pauza, 2003). Presently, the function of MVBs at these locations is unknown and largely unexamined.…”
Section: Distribution Of Mvbs In Neuronal Compartmentsmentioning
confidence: 99%
“…In some studies (Chu-Wang and Oppenheim, 1980, Omata and Schatzle, 1980; Pauziene and Pauza, 2003), the tissues were not immediately fixed. Delays of up to 8 hours (and lack of oxygen during this delay) could have rendered the terminals ischemic or dystrophic.…”
Section: Distribution Of Mvbs In Neuronal Compartmentsmentioning
confidence: 99%
“…Since then, the fine structure of hair cell receptoneural junctions (hair cell synapses) has been studied by many researchers in an attempt to characterize the structure and function of hair cells in the sensory epithelium of the acousticolateralis organs (Ades and Engstrom, 1974;Bodian, 1978Bodian, , 1980Bredberg, 1977;Engstrom, 1967a,b;Engstrom and Sjostrand, 1954;Iurato, 1961Iurato, , 1967Kimura, 1975;Kimura et al, 1964;Kimura and Wersall, 1962;Nadol, 1981Nadol, , 1983aOmata and Schatzle, 1980;Osborne, 1977;Rodriguez-Echandia, 1967;Smith, 1967;Sobkowicz et al, 1982Sobkowicz et al, , 1986Spoendlin, 1966Spoendlin, , 1969Wersall et al, 1961).…”
Section: Introductionmentioning
confidence: 99%